The complete guide to lifting heavy weights - Platt, G. F. (A & C Black Publishers Ltd., 2011)
Packed with information, tips, strategies and training plans, this is the definitive book for fitness professionals, coaches and sportspeople using or supervising the use of heavy weights. An essential publication in a discipline where poor instruction can lead to serious injury. Aimed at fitness professionals, coaches and sportspeople, this is the definitive guide to lifting maximum weights from beginner level through to advanced. This applies to those who wish to build body strength and bulk as well as people wanting to improve their performance in a range of other sports. Heavy weights are very popular in gyms but there is a lack of supervision and good instruction. This is not only dangerous to the gym user but also bad news for the gym, and it prompted the Register of Exercise Professionals (REPS) to authorise a range of new courses designed by the book's author. The Complete Guide to Lifting Heavy Weights is required reading for students taking these courses, and an essential guide for anyone who works with or supervises the use of heavy weights. As with all titles in the Complete Guide series it is packed with information, tips, strategies and training plans. Well-illustrated and authoritative, it covers everything you need to know to deal with heavy weights safely and successfully. The author is a former official of the Olympic and Commonwealth Games. Geoffrey Platt has taught weightlifting and strength & conditioning to elite national coaches, and managed anti-doping operations on behalf of the International Weightlifting Federation, the International Olympic Committee and the World Anti-Doping Agency.